PRKG1 mutation identified by whole-exome sequencing: a potential genetic etiology for He-Zhao deficiency. Issue 3 (29th August 2022) - Hu, Xiaowen; Wang, Dandan; Yang, Xuhan; Song, Zhongchen; Wang, Zuolin; Zhang, Juan; Wan, Chunling; He, Lin
Abstract : Objective: He-Zhao deficiency was originally described as a severe type of nonsyndromic hypodontia, and the causative gene locus was mapped to chromosome 10q11.2. The aim of this study was to identify potential genetic mutations that could cause He-Zhao deficiency. Methods: Patients with He-Zhao deficiency and their unaffected relatives of the large pedigree were investigated. The whole-exome sequencing using next-generation sequencing was employed to identify genetic variants. The data generated from the whole-exome sequencing using the Illumina Novaseq 6000 system were further analyzed by Burrows–Wheeler Aligner software, Sequence Alignment/Map tools and ANNOVAR tool. In vitro luciferase assay was used to investigate the effect of the detected mutation on gene expression. R environment was used to conduct t -tests. The study protocol was approved by the Research Ethics Committee of Bio-X Institutes, Shanghai Jiao Tong University (M2011004). Results: The exomes of five patients with He-Zhao deficiency and two of their unaffected relatives identified a mutation in PRKG1α as the molecular etiology of the disease. The variant c.-144 C>A of PRKG1 isoform 1 cosegregated with permanent tooth agenesis in 93 family members who were older than 12, at which time the primary teeth should have been replaced with permanent teeth. Functional studies suggested that the mutant allele promotes gene transcription by increasing its promoter activity. Conclusion: c.-144 C>A variant of PRKG1α involving odontoclast-associated root resorption is responsible for He-Zhao deficiency, unlike other forms of hypodontia, which typically involve odontoblast dysfunction.